Analisis Sistem Antrian Multi Chanel-Multi Phase pada Pelayanan Pembuatan Kartu Tanda Penduduk dengan Model Antrian (M/M/C):(GD/ ) di Disdukcapil Labuhanbatu Selatan - Rahmadani, Sri; Cipta, Hendra; Lubis, Riri Safitri (Universitas PGRI Semarang, 2026)
Public administrative services require speed, effectiveness, and efficiency to meet community expectations. At the Civil Registration Office of Labuhanbatu Selatan Regency, the issuance of identity cards (KTP) often experiences long queues, especially on specific days such as the beginning of the week and after major holidays. This study aims to analyze the performance of the current queuing system and determine the most appropriate model to improve service quality. A qualitative case study approach was used, supported by primary data obtained through direct observation of customer arrivals and service duration over five working days. Queueing theory was applied to test the distribution of arrivals and service times as well as evaluate system performance indicators. The results show that arrival patterns follow a Poisson distribution while service times follow an exponential distribution. The appropriate model for the system is the Multi Channel–Multi Phase (M/M/C):(GD/) queue. The highest utility rate occurred at entrance 2, reaching 30%, yet the average waiting time remained low at 0.18–0.24 minutes. Thus, the current queuing system is considered effective and capable of managing service demand without causing critical congestion.